Organogel-nanoemulsion containing nisin and D-limonene and its antimicrobial activity - Bei, Weiya; Zhou, Yan; Xing, Xuya; Zahi, Mohamed Red; Li, Yuan; Yuan, Qipeng; Liang, Hao (Frontiers in Microbiology, 2015)
The aim of this study was to investigate a novel delivery system containing D-limonene and nisin by food organogel-nanoemulsion and study its effect on the antimicrobial activity. Organogel-nanoemulsion containing with D-limonene and nisin or without nisin was prepared by a homogenization method. Factors that may affect the droplet size and stability of organogel-nanoemulsion such as pressure and surfactant to oil ratio were studied. The average droplet size decreased with pressure, and the organogel-nanoemulsion could achieve good stability at low surfactant to oil ratio. Positive effects and outstanding antimicrobial activities of organogel-nanoemulsion containing with D-limonene and nisin were confirmed by MICs comparison, growth curves of bacteria, scanning electron microscopy and determination of cell constituents’ release. Furthermore, the organogel-nanoemulsion applied as food preservative in milk also shown excellent antimicrobial performance. Overall, the research described in the current article show that organogel-nanoemulsion containing with D-limonene and nisin may be an effective antimicrobial system for the production and preservation of food.